18F-Fluorodeoxyglucose and 11C-methionine positron emission tomography in relation to methyl-guanine methyltransferase promoter methylation in high-grade gliomas. Issue 3 (March 2015) - Choi, Hongyoon; Bang, Ji-In; Cheon, Gi Jeong; Kim, Yong Hwy; Park, Chul-Kee; Park, Sung-Hye; Kang, Keon Wook; Chung, June-Key; Kim, Euishin E.; Lee, Dong Soo
Abstract : Introduction: Methylation status of the methyl-guanine methyltransferase (MGMT) promoter is associated with a favorable response to a DNA alkylating agent in high-grade gliomas. We analyzed PET scans of patients with high-grade gliomas to determine whether the MGMT methylation status affects the tumor metabolic characteristics. Patients and methods: Twenty-three patients with high-grade glioma, who were initially examined with 11 C-methionine (MET) and 18 F-fluorodeoxyglucose (FDG) PET, were retrospectively enrolled. MET and FDG PET images were coregistered to each other and quantitative uptake of MET or FDG was assessed using tumor-to-normal uptake ratio of the cortex (TNR). TNRs for MET and FDG PET were compared between the two groups classified by MGMT promoter methylation status. Results: Maximum TNRFDG of the MGMT methylated group was significantly higher than that of the MGMT unmethylated group (1.80±0.90 vs. 1.29±0.19; P =0.02). The MGMT methylated group also showed a trend for increased mean TNRFDG compared with the unmethylated group (0.85±0.21 vs. 0.72±0.11; P =0.10). There was no significant difference in TNRMET between the groups. In subgroup analyses with WHO grade 3 and 4, a trend for higher maximum TNRFDG was found in the MGMT methylated group compared with the unmethylated group. Conclusion: The MGMT methylated group showed higher glucose metabolism compared with the unmethylated group, whereas MET uptake did not show a significant difference. This suggests that MGMT methylation in high-grade gliomas could affect the tumor glucose metabolism. Thus, MGMT methylation status can cause a discrepancy in the prognostic prediction of high-grade gliomas by FDG PET, especially in patients scheduled for DNA alkylating chemotherapeutics. Abstract : Supplemental Digital Content is available in the text.